Handbook of research on effective project management through the integration of knowledge and innovation - Jamil, George Leal 1959- (Advances in IT Personnel and Project Management (AITPPM) Book Series, 2015)
"This chapter bridges the gap between knowledge management and project management practices by providing both classical and modern views on their relationship, discussing principles, practices, methods, and real case studies"-- Provided by publisher.